The Development of Teaching Materials of Writing Javanese News Texts using Local Wisdom for Grade X High School/ Vocational Schools (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this study was to describe the characteristics of the need for the teaching materials to write news texts and a model for developing the teaching materials for writing news texts in Javanese using local wisdom for grade X students of SMA/ SMK. The study was conducted using the Research and Development design. Teaching material for writing news texts was developed by applying four aspects of the feasibility of teaching materials consisting of material, linguistic, presentation, and graphic aspects. In addition, teaching material products were arranged in accordance with the principles of developing teaching materials such as meaningfulness, authenticity, cohesiveness, functioning, communicative performance, relevance, evaluation, relevance, consistency, and adequacy. The draft of the instructional materials compiled consists of the beginning, contents, and closing. The teaching material development products are arranged according to the characteristics of students who expect local content. The content of local wisdom is placed in every part of the teaching materials such as the front cover, the beginning of the chapter, the presentation of news texts, materials, and assignments. By using the content of local wisdom, students are expected to be able to understand the values ​​contained in it and appreciate and love their culture.